Economic Valuation of Moratorium and Transhipment Policy to Tuna Fisheries Business, Study Case in Bitung, North Sulawesi - Zulbainarni, Nimmi; Sukarsih, Yayuk; Jahroh, Siti; Abdullah, Asaduddin (School of Business, Bogor Agricultural University (SB-IPB), 2022)
The policy of moratorium on ex-welding vessels, according to Ministerial Regulation No. 56/2014, has an impact on tuna fishery conditions. Behind this policy is due to the heavy losses from the fisheries sector caused by the operation of these ex-foreign ships. This study evaluated the impact of policy by production surplus measurement techniques. The survey was conducted on capture fisheries companies, fish processing companies, and traditional processing groups. Data were analyzed by economic valuation using the extended cost-benefit analysis (ECBA) approach. The study results showed that as long as this policy is implemented, it will cause a decrease in the benefits of 9 tuna fisheries business actors by Rp1.23 trillion per year. Economic and social impacts of Rp 2.63 trillion per year, consisting of economic impacts of Rp1.35 trillion per year and social impacts of Rp1.28 trillion per year, which caused 19,972 people to lose their job. Keywords: cost cost benefit analysis, economic impact, social iImpact, valuation